Adiposity, Change in Adiposity, and Cognitive Decline in Mid‐ and Late Life. Issue 6 (1st March 2017) - West, Nancy A.; Lirette, Seth T.; Cannon, Victoria A.; Turner, Stephen T.; Mosley, Thomas H.; Windham, Beverly G.
Abstract : Objectives: To examine associations between adiposity and adiposity change (loss, stable, gain) and subsequent longitudinal cognitive performance in African Americans in mid and late life. Design: Cohort study using linear mixed models. Setting: Genetic Epidemiology Network of Arteriopathy. Participants: African‐American sibships with hypertension in Jackson, Mississippi (N = 1, 108). Measurements: Waist circumference and body mass index (BMI) were measured at two examinations 5 years apart. Stable adiposity was defined as values within 5% of the first measure. A composite cognitive Z ‐score was derived from individual cognitive test Z ‐scores at two study visits 6 years apart. Results: Larger waist circumference was associated with greater rate of cognitive decline during follow‐up (beta = −0.0009 per year, P = .001); BMI, change in waist circumference, and change in BMI were not associated with rate of decline. Loss of adiposity in midlife was associated with higher cognitive Z ‐scores in middle‐aged individuals, and loss of adiposity in late life was associated with lower Z ‐scores in older adults ( P = .01 for interaction between waist circumference and age; P = .04 for interaction between BMI and age). Simultaneous inclusion of waist circumference and BMI in the cross‐sectional model suggested an association between larger waist circumference and poorer cognitive performance (beta = −0.009, P = .006) and between higher BMI and better cognitive performance (beta = 0.014, P = .06). Conclusion: The results suggested a differential pattern of the relationship between adiposity and cognition according to age (mid‐ or late life) and regional distribution of adiposity.